Computational study on the reaction collisions for the state-to-state process of N(4 S)+NO(2Π)→O(3 P)+N2(X 1Σ+ g) - Wang, Ya-Xin; Zhang, Hong; Cheng, Xin-Lu (Molecular physics, 2021)
Quasi-classical trajectory method has been employed in the theoretical calculations for the state-to-state processes of the reaction N( 4 S)+NO( 2 Π)→O( 3 P)+N 2 (X 1 Σ+ g) over a temperature range of 300 K ≤ T ≤ 10,000 K on Global triplet potential energy surface (PES) for N 2 O system. The thermal rates calculated for the N + NO→O + N 2 reaction show a great agreement with the previous theoretical and experimental results. The results obtained herein fill the gaps in the existing data for the state-to-state processes in the N 2 O system and could be applied to large temperature ranges relevant to the model of hypersonic gas flows. In addition, the vibrational relaxation rate coefficients of the non-reactive collision between N atom and NO molecule in the low vibrational excited state were calculated and reported.